Strategi Pemberdayaan Masyarakat melalui Kemitraan oleh Omah Jamur Tepian Langit: Community Empowerment Strategy through Partnership by Omah Jamur Tepian Langit (Jurnal Riset Agribisnis dan Peternakan, 2024)
Oyster mushrooms are commodities that have a wide market share, but cannot be fulfilled by farmers. Partnerships between Omah Mushroom Tepian Langit and the community are needed to increase oyster mushroom production and community income. This study aims to identify and analyze community empowerment programs through oyster mushroom cultivation partnerships in Sendangagung Village, Minggir District, Sleman Regency. The research method uses a qualitative approach. The informant of this study is the owner of Omah Mushroom Tepian Langit. Observations and interviews were conducted to collect data. The results showed that the empowerment process in the community in cultivating oyster mushrooms went through 3 stages, namely, the stage of awareness, capacity, and empowerment. The awareness stage is carried out with discussion and socialization. The capacity stage is carried out by training in the cultivation of oyster mushrooms. The empowerment stage is carried out by providing facilities in the form of capital in the form of mushroom baglogs.
Keywords: Mushroom cultivation; Partnership; Empowerment